Global warming potential of a residential building construction in Malaysia using the life cycle assessment (LCA) approach - Abd Rashid, Abd Rashid; Yusoff, Sumiani (Construction Research Institute of Malaysia, 2018)
Building industry consumes substantial natural resources and produces considerable greenhouse gas emission. This paper presents a life cycle assessment approach to assess Global Warming Potential (GWP) of a residential building in Malaysia. The results show that building element that uses a cement-based material such as concrete contributed the highest GWP in comparison to other materials. In the construction phase, temporary timber formwork has the highest GWP. The results also show that the semi-detached house has higher GWP per m 2 compared to flats. The findings from this research can serve as the benchmark for LCA for buildings in Malaysia.